2019
DOI: 10.21303/2504-5571.2019.00995
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Emotional Determinants on the Food Choices of the Portuguese

Abstract: Food choices are influenced by many factors, such as emotional. When people eat, driven by emotional factors, they often lose control, which may lead to eating disorders. Therefore, this work aimed at studying the influence that emotional determinants had on people's food choices. It was undertaken a descriptive cross-sectional study by means of a questionnaire on a non-probabilistic sample of 1314 participants. The data was collected among a sample of the Portuguese population and measured if people´s food ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Being alone facilitates individuals with EmE taking more food than being with an unfamiliar dining companion, possibly because being alone is perceived as not requiring impression management tactics while eating. The findings support previous research that being alone encourages individuals with EmE to eat more (Guiné et al, 2019). Additionally, this study complements the research of Godor (2020), which called for research investigating EmE with unfamiliar peers using objective measurement (Godor et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Being alone facilitates individuals with EmE taking more food than being with an unfamiliar dining companion, possibly because being alone is perceived as not requiring impression management tactics while eating. The findings support previous research that being alone encourages individuals with EmE to eat more (Guiné et al, 2019). Additionally, this study complements the research of Godor (2020), which called for research investigating EmE with unfamiliar peers using objective measurement (Godor et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, high-calorie foods, such as pizza, are perceived as more satiating with larger portions (Cobo et al, 2022;Zahrah et al, 2023). Consequently, it has been demonstrated that EmE is frequently linked to overeating and a high body mass index (Guiné et al, 2019). However, are there other factors that make individuals with EmE restrict their eating?…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the number of hours/day spent r in front of the TV or computer, we obtained positive correlations for both age and BMI. (1) N = number of participants; (2) BMI = body mass index; (3) p < 0.05 is considered significant; (4) Spearman test; (5) Spearman correlation; (6) Pearson test; (7) r = Pearson correlation; (8) NA = not applicable; this group was excluded from the analysis due to low number of cases; (9) T-test; (10) Kruskal-Wallis test; (11) ANOVA test; (12) Mann-Whitney test; r x = correlation between hours/day spent watching TV or in front of the computer and age; r y = correlation between hours/day spent watching TV or in front of the computer and BMI; (12) N.P. = not performed, because it is not relevant for the current research to compare BMI according to different pathologies (obesity is included, and there are subjects with more than one of the conditions asked).…”
Section: Resultsmentioning
confidence: 99%
“…In the scientific literature, many variables have been used to analyze consumer behavior in the food market, the most frequent being the socio-demographic factors, motivations and attitudes, religious traits, and cultural and social background, along with geographical variability and lifestyle [6][7][8].…”
Section: Introductionmentioning
confidence: 99%